Sobre a ocupação do Neolítico inicial do Norte de Portugal - Sanches, Maria de Jesus (2003)
This article aims to discuss human settlement in northern Portugal, between the beginning of the Holocene and the middle of the IVth millennium BC from the hunter-gatherer groups who inhabited and sacralized the Alto Douro region during the Upper Paleolithic, to the Neolithic communities who, during the IVth millennium, erected megalithic burial monuments. Both archaeological and environmental contexts are discussed here. The main discussion points include: a) Archaeological remains testify to the existence of human occupation during the Epipaleolithic/Mesolithic period. These include habitats (one of them dating back to the VIIth millennium BC) and shelters with wall paintings. The hypothesis of a continuous regional settlement from the Upper Paleolithic to the Early Neolithic must be seriously considered, although new data are needed. b) Early Neolithic occupation has been identified at several sites, from the VIth to the middle of the IVth millennium BC. Diverse archaeological evidence has been recovered from these sites. Their main features include decorated and/or non-decorated pottery, microlithic and macrolithic artefacts, axes, grinding stones, macrobotanical remains testifying to the existence of agriculture (cereals and legumes) and gathering practices (acorns, hazelnuts, pine kernels). Animal husbandry is recorded in two of the sites. c) These habitats dating back to the Early Neolithic are situated in three different regions in northern Portugal: Serra da Aboboreira (Douro Litoral province), Serra de Passos and Vila Nova de Foz Côa area (both in the Trás-os-Montes and Alto Douro provinces). These are restricted geographic areas where systematic archaeological investigation has been carried out, which might provide a distorted image of human settlement during this period. Other areas may also have been occupied during this period, but investigation is more sparse and unfocused. d) Human settlement is recorded in different types of habitat, such as open-air sites and rock shelters, situated at different altitudes. Some of the rock shelters display Neolithic paintings. These settlements are located in mountain, plateau and valley areas, and seem to testify to the existence of a high degree of mobility. This mobility might have originated as only living or logistic arrangements, as a result of socioeconomic conditions, and may have been gradually reduced with the development of plant and animal husbandry. e) How were the new Neolithic products received by the different local communities? Archaeological evidence is scarce; however, it seems possible that this transmission might have been carried out following normal inter-community relations. However, the hypothesis of the arrival and spread of new small groups, familiar with the new Neolithic innovations, must also be considered.